Prognostic and Clinicopathological Significance of PD-L1 in Patients With Bladder Cancer: A Meta-Analysis - Lei Zhu; Jin Sun; Ling Wang; Zhigang Li; Lei Wang; Zhibin Li (Frontiers Media S.A., 2019)
Background: The prognostic role of programmed cell death-ligand 1 (PD-L1) in bladder cancer has been investigated in previous studies, but the results remain inconclusive. Therefore, we carried out a meta-analysis to evaluate the prognostic significance of PD-L1 in patients with bladder cancer.Methods: The electronic databases PubMed, Embase, Web of Science, and Cochrane Library were searched. The association between PD-L1 expression and survival outcomes and clinicopathological factors was analyzed by hazard ratios (HRs) or odds ratios (ORs) and 95% confidence intervals (CIs).Results: A total of 11 studies containing 1,697 patients were included in the meta-analysis. High PD-L1 expression was associated with poor overall survival (OS) (HR = 1.83, 95% CI = 1.24-2.71, p = 0.002). There was nonsignificant association between PD-L1 and recurrence-free survival (RFS) (HR = 1.43, 95% CI = 0.89-2.29, p = 0.134), cancer-specific survival (CSS) (HR = 1.51, 95% CI = 0.80-2.87, p = 0.203), or disease-free survival (DFS) (HR = 1.53, 95% CI = 0.88-2.65, p = 0.13). Furthermore, high PD-L1 was significantly correlated with higher tumor stage (OR = 3.9, 95% CI = 2.71-5.61, p < 0.001) and distant metastasis (OR = 2.5, 95% CI = 1.22-5.1, p = 0.012), while PD-L1 overexpression was not correlated with sex, tumor grade, lymph node status, and multifocality.Conclusions: The meta-analysis suggested that PD-L1 overexpression could predict worse survival outcomes in bladder cancer. High PD-L1 expression may act as a potential prognostic marker for patients with bladder cancer.